Why does the Media Disregard Internal Fact-Checking? The Fact-Checking Logic Determination in the Case of Ukrainian Media - Zakharchenko, Artem; Nagorna, Anna; Chekmyshev, Oleksandr (Information & Media, 2025)
In this article, fact-checking logic is introduced as part of general media logic. This system is responsible for news editors’ decisions on whether to believe a fact or check it before publishing the news. Through the qualitative research applying semi-structured interviews with seven news editors of the leading Ukrainian online media, we have revealed that their fact-checking logic is built on the efforts for reconciliation between accuracy and other factors like speed, social media algorithms, audience metrics, virality, and the management style of editors-in-chief. We have discovered that publishing news without 100% confidence is common. The participants justified the absence of fact-checking with the publishing pressure, bad mood, the author’s or boss’s assurance, and many other excuses. They confess that news publications often appear to be inaccurate or even fake. We discuss incentives, drivers, and decision-making processes for fact-checking in the Ukrainian media and observe that mostly the inaccurate information published by the Ukrainian media can be attributed to cases when news editors were not completely confident in their decision to publish some fact, but not to the situations when they wrongly have 100% confidence. We suggest a way to solve this problem through the public declaration of fact-checking media logic principles.